Fungal Mediated Generation of Mammalian Metabolites of Fenofibrate and Enhanced Pharmacological Activity of the Main Metabolite Fenofibric Acid - Shyam Prasad, G.; Govardhan, P.; Girisham, S.; Reddy, S.M. (Drug Metabolism Letters, 2014)
Different fungi viz. Aspergillus niger NCIM 589, A.ochraceous NCIM 1140, Cunninghamella blakesleeana NCIM 687, C. echinulata NCIM 691, Rhizopus stolonifer NCIM 880, Mucor rouxi MTCC 386, Trichothecium roseum NCIM 1147 were screened for their potential to biotransform anti-hyperlipidemia and anti-hypertriglyceridemia drug, fenofibrate to fenofibric acid, the active metabolite and other mammalian metabolites. Among the fungi screened C. blakesleeana transformed fenofibrate to fenofibric acid and other three metabolites. HPLC, LC-MS/MS analysis and previous reports confirmed the transformation of fenofibrate and metabolites as fenofibric acid (M1), reduced fenofibric acid (M2), reduced fenofibric acid taurine conjugate (M3), reduced fenofibric acid ester glucuronide (M4), the mammalian metabolites reported previously. The results proved the potential of C.blakesleeana NCIM 687 in the production of mammalian phase I (M1 and M2) and phase II (M3 and M4) metabolites in large quantities and also as an in vitro model for drug metabolism studies.
Keywords: Fenofibrate